Engaging in Educational Research Revisiting Policy and Practice in Bangladesh (Education in the Asia-Pacific Region: Issues, Concerns and Prospects,, 2018)
This book reflects the paradigm shift now manifesting in Bangladesh's education system by highlighting recent empirical research. It shares essential insights by presenting research conducted on diverse aspects of current day education in Bangladesh, including policy and governance, equity, access and participation, curriculum and pedagogy, assessment, and education programs and projects run by NGOs. Further, it offers a platform for these unique studies to be showcased and disseminated to scholars and researchers from developing and developed countries alike, and represents a unique reference resource for the education research community in Bangladesh, Asia and all over the world. 'Although Bangladesh is one of the largest countries in the world, with its population now approaching 165 million, there is a dearth of good scholarship on recent developments in its system of education. This much needed and timely book fills this inexcusable gap. It contains a number of excellent papers that not only describe Bangladesh's complex system of education but also interrogate the nation's struggle to realise its long cherished goals of access, quality and equity in education.' -Fazal Rizvi, Professor of Global Studies in Education, The University of Melbourne, Australia 'In its journey of becoming a Developing Nation, Bangladesh's need for research-based decision making is of immense importance. Strongly based on a carefully selected range of studies, 'Engaging in Educational Research: Revisiting Policy and Practice in Bangladesh' is a cutting-edge publication with contributions from a promising group of visionary researchers at home and abroad. This book includes, among other themes, three key areas of education, along with a wide range of issues around Bangladesh and the contemporary world. I firmly believe that this book will play a significant role in providing insights into the complex nature of engagement of different stakeholders and provide a clear guideline towards quality education. I anticipate that the readers will be highly benefited, which in turn will facilitate early achievement of Sustainable Development Goals.' -Professor Dr. Siddiqur Rahman, Member, Bangladesh National Education Policy 2010 Formulation Committee .